Variasi Genetik Ikan Hias Clown, Amphiprion ocellaris - Sari Budi Moria; Ida Komang Wardana; Gusti Ngurah Permana; Ahmad Muzaki; Ketut Maha Setiawati (Universitas Gadjah Mada, 2007)
Evaluation of genetic variation of wild clown fish, Amphiprion ocellaris was conducted to collect basic knowledge in order to develop sustainable ornamental fish breeding under controled condition. Clown fish samples were collected from three locations, i.e. Bali, Madura, and South Sulawesi waters. PCR amplification of mt-DNA by using universal primer obtained single band with molecule weight of 461 bp. RFLP of mt-DNA with Hinf I, Mbo I and Nla III restriction enzymes showed that the highest genetic variation as 0.581 was found from South Sulawesi population and the lowest as 0.382 from Bali, while Madura population has genetic variation of 0.456. Genetic distance of clown fish from South Sulawesi and Madura was closer (0.107) comparing to clown fish from Bali population (0.270).